Seasonal and daily fluctuations of aquatic birds in Saco da Fazenda, Itajaí-sc - Francine Corrêa Manoel; Joaquim Olinto Branco; Edison Barbieri (O Mundo da Saúde, 2011)
Saco da Fazenda ecosystem, in spite of the impact caused by the flow of effluent domestic and industrial sewage coming from Itajaí-Açu River, shelters a great diversity of birds. The knowledge of the composition of avifauna becomes crucial in the characterization of this environment, since in threatened ecosystems, as estuaries, we may verify alterations in biodiversity and abundance due to the influence of adjacent areas on the ecosystem. From July 2006 and April 2007 we did biweekly censuses in the assembly of aquatic birds, with two hour intervals from 8:00 P.M. and 2:00 AM. We registered 29 aquatic birds species, distributed in 25 genres and 13 families, being 11 of constant occurrence (37.9%), six accessory (20.6%) and 12 species of casual presence (41.3%). We found expressive differences in the abundance of aquatic birds among biweekly and daily intervals. Daily average fluctuation presented a small increment from the first interval of counting, and reached the highest values from 14:00 to 16:00 PM (256.2 ± 24.9), with a consecutive lesser value around 18:00 PM (56,3 ± 14,6), last schedule of census.